Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Berpikir Kreatif Siswa pada Pembelajaran Seni Budaya dan Prakarya Kelas IV Sekolah Dasar - Arif Khoirudin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the Project Based Learning model on the creativethinking skills of fourth grade students of MI Muhammadiyah Kaweron Muntilan. This study used a Pre-Experimental Design type of research with One Group Pre-test Post-test Design model. The samples were 26 students. By using data collection methods in the form of description tests and performance assessments of creative thinking skills. Thevalidity test for the creative thinking ability description test used the Pearson Formula.The reliability test used Cornbach's Alpha with the help of IBM SPSS 25 version. Inaddition, the researcher used the normality test. Data analysis used parametric statisticaltechnique, namely Paired Sample t-Test.The results showed that the calculation of the average score of the post-test descriptiontest was 88.8 which was greater than the test results in the pre-test with an average valueof 62.7. Calculation of performance assessment on student project making activities withan average of 87.5. This is evidenced by the results of the Paired Sample t-Test analysiswhich has mean difference between pre-test and post-test of 26,15385 with a t-value of32,717 with a significance value of 0.000 <0.05, meaning that there is a significantdifference between the results of the pre-test and post-test. Which used the Project BasedLearning Model in the subjects of Cultural Arts and Crafts. The results of this study canbe concluded that the use of the Project Based Learning Model has a significant effect onstudents' creative thinking skills in the subjects of Cultural Arts and Crafts.